2005
DOI: 10.1128/iai.73.6.3210-3218.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sialic Acid and Complex Carbohydrate Biosynthesis in Biofilm Formation by Nontypeable Haemophilus influenzae in the Chinchilla Middle Ear

Abstract: Nontypeable Haemophilus influenzae (NTHI) is an important pathogen in respiratory tract infections, including otitis media (OM). NTHI forms biofilms in vitro as well as in the chinchilla middle ear, suggesting that biofilm formation in vivo might play an important role in the pathogenesis and chronicity of OM. We've previously shown that SiaA, SiaB, and WecA are involved in biofilm production by NTHI in vitro. To investigate whether these gene products were also involved in biofilm production in vivo, NTHI str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
137
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 28 publications
5
137
0
5
Order By: Relevance
“…However, it is noteworthy that we were consistently able to recover viable bacteria from middle ear effusions of those animals infected with NTHi 86-028NP licD that had recoverable middle ear effusion fluids. This finding is reminiscent of prior work showing that some variants can persist in the planktonic phase within the middle ear despite failing to form biofilms (18).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…However, it is noteworthy that we were consistently able to recover viable bacteria from middle ear effusions of those animals infected with NTHi 86-028NP licD that had recoverable middle ear effusion fluids. This finding is reminiscent of prior work showing that some variants can persist in the planktonic phase within the middle ear despite failing to form biofilms (18).…”
Section: Discussionsupporting
confidence: 78%
“…A large body of work shows that populations of NTHi in vivo contain variants that are sialylated (18,24) and PCho ϩ (45,52,53). Moreover, prior work has clearly shown that NeuAc promotes biofilm formation and bacterial persistence in animal models of NTHi disease (4,18,43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations